POLITIK ISLAM SEBAGAI ILMU DAN SEBAGAI GERAKAN; STUDI DESKRIPTIF DUNIA ISLAM - Muhamad Fajar Pramono (UNIDA Gontor, 2018)
Islamic toughtsclearly explain about political issues. Even though, in development and implementation, it is not easy to get an ideal example. The debate among scholars and scientists is quite hard either in the mass media or in scientific forums, and it often fails to draw conclusions that are bright and fair. As an ideal example at the implementation level, it is also not easy to find agreements among Muslim practitioners, whether it is a model of the political system in Saudi Arabia, the politics of Indonesia, Malaysia, Brunei, Iran or the Turkish political system. In addition to external factors, global hegemony of thought and politics, the internal conditions of the Muslim community are also inseparable, especially among scientists and scholars and their politicians who are not serious about studying and animating the wealth of Islamic political treasures. This article will explain Islamic politics with two perspectives, namely: Islamic politics as a science (academic level) and Islamic politics as a movement (practical / implementative level). It is hoped that this article can provide theoretical answers and be able to explain political phenomena in the Islamic world in general and especially the phenomenon of Islamic politics in Indonesia.